Teacher Collegiality in a Remote Australian School - Lucy Jarzabkowski (Journal of Research in Rural Education, 2003)
Teachers' lives and teachers' work remain important areas of educational research today, particularly given the influence of school-based management and the significance of shared leadership in schools. Almost nowhere do the two research fields intersect more closely than in the remote school setting, where teacher turnover is high and the recruitment of experienced teachers is difficult. This article investigates the realities of teachers living and working together in a small school located in a remote, northern Australian, Aboriginal community. It highlights environmental conditions that can be challenging for teachers, both new and recent graduates and those with experience. The research draws attention to collegial community building in a geographically remote location, particularly the development of material and emotional support systems, as a means of managing some of these challenges.